Studies on the hepatic and renal status of patients with sickle cell disease from western zone of Maharashtra, India - Garg, Deepa; Satam, Neha; N., Nimisha; Marar, T.; Patil, V. W. (International Journal of Research in Medical Sciences, 2018)
Background: Sickle cell disease (SCD) is the most common inherited monogenic genetic disorder in Indian tribal and non-tribal population. This condition is caused by mutations in the hemoglobin gene and inherited in an autosomal recessive pattern. Pathogenesis in SCD varies widely from patient to patient. Most of the infections affect SCD pathogenesis, so early diagnosis of the same is important. Methods: The present study was designed to evaluate the biochemical parameters to assess the hepatic and renal status in SCD subjects from west zone of Maharashtra, India. Patients with sickle cell disease (n=50) from primary health centres of Palghar were included in this study and age and sex matched healthy persons (n=50) were controls. Informed written consent was obtained from all the study subjects. Results: Our findings showed that Aspartate trasaminase (AST), Alanine transaminase (ALT), bilirubin and creatinine increased significantly above normal level in SCD subjects. Albumin and urea levels in SCD were found to have decreased in the SCD subjects. There is a slight increase in uric acid and creatinine levels; this indicates an adverse effect on hepatic function and moderate effect on renal function in sickle cell anemia patients. Most common events of SCD pathogenesis, can be categorized into hemolytic events and vaso-occlusive crisis-based events. Adverse effect on hepatic function can lead to further hemolytic events. Conclusions: Although specific biomarkers related to these different events needs to understand for assessment of pathogenesis, the ones we have studied can be useful to assess the status of hepatic and renal function to follow the effectiveness of therapeutic interventions.